2008
DOI: 10.3748/wjg.14.53
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of fecal calprotectin in determining disease activity of ulcerative colitis

Abstract: AIM:To investigate possibility and clinical application of fecal calprotectin in determining disease activity of ulcerative colitis (UC). METHODS:The enzyme-linked immunosorbent assay (ELISA) was used to measure the concentrations of calprotectin in feces obtained from 66 patients with UC and 20 controls. C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), acid glycoprotein (AGP) were also measured and were compared with calprotectin in determining disease activity of UC. The disease activity of UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 32 publications
9
70
0
1
Order By: Relevance
“…Also should be reiterated that fecal calprotectin cannot distinguish infectious bowel disease from IBD, so appropriate culture studies should always be performed before diagnosing a patient as IBD when the level of fecal calprotectin is high because in both conditions there is heavy invasion by neutrophils ; the main mother cell of calprotectin (9).In the other hand our results showed significant difference between UC patients according to presence or absence of signs of activity with higher values in active disease which simply explained by same concept that during activity there is huge invasion by neutrophils. These results confirm the results of Jun-Ying Xiang et al (22).which concluded that fecal calprotectin concentration in the patients with active UC was significantly higher than that in the inactive UC. They also found a significant difference was also found in the patients with active UC of mild, moderate and severe degrees but they did not determine certain cut off value of fecal calprotectin differentiating active from inactive UC.…”
Section: Figuresupporting
confidence: 83%
“…Also should be reiterated that fecal calprotectin cannot distinguish infectious bowel disease from IBD, so appropriate culture studies should always be performed before diagnosing a patient as IBD when the level of fecal calprotectin is high because in both conditions there is heavy invasion by neutrophils ; the main mother cell of calprotectin (9).In the other hand our results showed significant difference between UC patients according to presence or absence of signs of activity with higher values in active disease which simply explained by same concept that during activity there is huge invasion by neutrophils. These results confirm the results of Jun-Ying Xiang et al (22).which concluded that fecal calprotectin concentration in the patients with active UC was significantly higher than that in the inactive UC. They also found a significant difference was also found in the patients with active UC of mild, moderate and severe degrees but they did not determine certain cut off value of fecal calprotectin differentiating active from inactive UC.…”
Section: Figuresupporting
confidence: 83%
“…Nevertheless, although fecal calprotectin is not specific it is exceptionally useful in assessment of inflammatory bowel disease. This examination is worth of recommendation especially in children in whom intestinal neoplasm is extremely rare and its non-invasiveness and painlessness causes that it is a promising diagnostic tool, which can supplement the standard methods [7,15,18,27,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Langhorst et al and Alian et al found a good correlation between the concentrations of fecal lactoferrin, fecal calprotectin, Rachmilewitz Activity Indices, CRP, and blood leukocytes in ulcerative colitis patients (7,42). Also, Xiang et al and Mahmoud et al founded a good correlation between fecal calprotectin, ESR, CRP, and ulcerative colitis activity index in ulcerative colitis patients (8,10). Kilic et al found a significant correlation between TGF-B1 levels and CRP, whereas no significant correlation was established between the other parameters ( blood leucocytes, ESR, fibrinogen level, and platelet count) ( 45 ).On the other hand, Irena et al found a good correlation between TGF-B1 and the concentrations of CRP and platelet count and can be used for evaluation of inflammatory activity in ulcerative colitis and to a lesser extent can also be used for evaluation of inflammatory activity in crohn's disease (41).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we try to evaluate any relationship that might exist between the mucosal neutrophil infiltration represented by Lactoferrin, calprotectin, TGF-B1, CRP, sedimentation rate, and the ulcerative colitis disease activity represented by Rachmilewitz criteria (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation